Comparison between the speech and Language Therapist’s Transversal / Generic Competences in Spain and Europe. Reformulation - García-Atarés, Natividad; Santiago Pardo, Rosa Belén; Jimeno-Bulnes, Natalia (Revista de Investigación en Logopedia, 2022)
Since the beginning of the educational model of the European Higher Education Area more than 20 years ago, the training of undergraduate students has as a priority aim the acquisition of professional skills that respond to social reality. The definition and acquisition of these competences is essential for the professional’s continuous training, the design and development of educational programmes and the implementation of healthcare services. The objective is to carry out a comparative analysis of the speech and language therapist’s transversal/generic professional competences in Spain and Europe. The lists of transversal competences collected in the White Book of the Degree in Speech and Language Therapy, the CIN order, and the list of generic competences established in the international project NetQues (Network for Tuning Standards and Quality of Education programmes in Speech and Language Therapy across Europe) have been used. A qualitative analysis of both lists has been performed in order to identify similarities and differences among them. The relationships between the transversal competences in Spain and the generic competences in Europe are established; a complete and clear list of transversal competences is proposed. This list of transversal competences is a potential reference for Spanish and ideally European speech and language therapists. Concerning conclusions, there are equivalences between Spanish transversal competences and those agreed in the European NetQues project. Spanish and European transversal competences can be grouped together and reduced in number. The reformulation of transversal competences is an opportunity to facilitate their management by interested students, trainers, and professionals.
Keywords: Generic competence; transversal competence; European Higher Education Area (EHEA); speech and language therapy; profession